The spindle position checkpoint: how to deal with spindle misalignment during asymmetric cell division in budding yeast. (21st May 2008) - Fraschini, Roberta; Venturetti, Marianna; Chiroli, Elena; Piatti, Simonetta
Abstract : During asymmetric cell division, spindle positioning is critical to ensure the unequal segregation of polarity factors and generate daughter cells with different sizes or fates. In budding yeast the boundary between mother and daughter cell resides at the bud neck, where cytokinesis takes place at the end of the cell cycle. Since budding and bud neck formation occur much earlier than bipolar spindle formation, spindle positioning is a finely regulated process. A surveillance device called the SPOC (spindle position checkpoint) oversees this process and delays mitotic exit and cytokinesis until the spindle is properly oriented along the division axis, thus ensuring genome stability.